The Role of Financial Technology and Intellectual Capital in Improving Bank Performance in the Digital Era - Panjaitan, Raya; Siahaan, Jeremy; Julyanthry (Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid evolution of financial technology (fintech) and the strategic role of Intellectual Capital (IC) have transformed the banking sector, State-owned Enterprises banks in Indonesia. This study aims to examine the individual and combined effects of fintech and IC on the financial performance of State-owned Enterprises banks from 2021 to 2023. Employing panel data regression analysis with 30 observations from five State-owned Enterprises banks, the research measures fintech via mobile banking transaction volume and IC through Value Added Human Capital (VAHU), Structural Capital Value Added (SCVA), and Value-Added Capital Employed (VACA), with Return on Assets (ROA) as the performance indicator. Results indicate that fintech has no significant impact on ROA, while VAHU significantly enhances financial performance. SCVA and VACA show no notable effects. Collectively, fintech and IC significantly influence performance. These findings underscore the importance of optimizing human capital and strategically integrating fintech to boost efficiency and competitiveness, offering valuable insights for state-owned enterprises banks’ strategic planning and policy development in a digital era.